2005
DOI: 10.1002/cne.20420
|View full text |Cite
|
Sign up to set email alerts
|

Developmental expression of a tyramine receptor gene in the brain of the honey bee, Apis mellifera

Abstract: This study reveals that the tyramine receptor gene, Amtyr1, is expressed in the developing brain, as well as in the brain of the adult worker honey bee. Changes in levels of Amtyr1 expression were examined using Northern analysis. Age-related increases in Amtyr1 transcript levels were observed not only during metamorphic adult development, but also in the brain of the adult worker bee. RNA in situ hybridization revealed the pattern of Amtyr1 expression. Cell bodies staining intensely for tyramine receptor-gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 60 publications
4
44
1
Order By: Relevance
“…Although we did not detect an additional start codon on exon 1, we cannot exclude the possibility that there is another start codon in the unknown 5′-part of the Amtyr1∆II mRNA. Northern blot analysis showed that the tyramine receptor Amtyr1 mRNA is about 9.5 kb (Mustard et al, 2005). Combining the known sequence information (Blenau et al, 2000) with our new sequence information from cloning PCR and RACE PCR fragments, the known Amtyr1 mRNA comprises only about 4.5 kb.…”
Section: Results and Discussion Differential Splicing Of The Tyraminementioning
confidence: 69%
“…Although we did not detect an additional start codon on exon 1, we cannot exclude the possibility that there is another start codon in the unknown 5′-part of the Amtyr1∆II mRNA. Northern blot analysis showed that the tyramine receptor Amtyr1 mRNA is about 9.5 kb (Mustard et al, 2005). Combining the known sequence information (Blenau et al, 2000) with our new sequence information from cloning PCR and RACE PCR fragments, the known Amtyr1 mRNA comprises only about 4.5 kb.…”
Section: Results and Discussion Differential Splicing Of The Tyraminementioning
confidence: 69%
“…In addition to providing the means by which to further characterize Drosophila OCT/TYR GPCRs these clones served as nucleic acid hybridization probes that were used to identify and isolate homologous receptor sequences from several invertebrate species (Vanden Broeck et al, 1995;von Nickisch-Rosenegk et al, 1996;Gerhardt et al, 1997a;Gerhardt et al, 1997b;Reale et al, 1997;Baxter & Barker, 1999;Blenau et al 2000;Chang et al, 2000;Poels et al, 2001;Rex & Komuniecki, 2002;Ohta et al, 2003;Farooqui et al, 2003;Farooqui et al, 2004;Grohmann et al, 2003;Bischof & Enan, 2004;Balfanz, 2005;Molaei et al, 2005;Mustard et al 2005;Rex et al, 2005;Dacks et al, 2006). These clones have also been instrumental in identifying the important structural features that particpate in the binding of ligand and coupling of the the receptor to its effectors (Chatwin et al, 2003;Huang, 2003;Ohta et al, 2004).…”
Section: Invertebrate Trace Amine-activated Receptorsmentioning
confidence: 99%
“…The honeybee genome contains sequences for two tyramine receptors (Cazzamali et al, 2005;Hauser et al, 2006). One of these tyramine receptors (AmTYR1) decreases intracellular cAMP concentrations ([cAMP] i ) when activated (Beggs et al, 2011;Blenau et al, 2000;Mustard et al, 2005), while the second tyramine receptor (AmTYR2) increases [cAMP] i after activation (Reim et al, 2017). Interestingly, this receptor acts similarly to four of the five honeybee octopamine receptors (Balfanz et al, 2014), which all increase [cAMP] i after activation.…”
Section: Introductionmentioning
confidence: 99%